ANALYSIS OF HAZARDOUS AND TOXIC SOLID MEDICAL WASTE MANAGEMENT IN PURWOREJO HOSPITAL - Arumdani, Intan Sekar; Ilma, Khaira; Salsabila, Rizky Aulia; Nurany, Hanung (Jurnal Manajemen Kesehatan Indonesia, 2025)
Hospitals and health care facilities generate increasing amounts of solid medical waste each year. Improper treatment of this waste poses a potential risk for disease transmission. The Ministry of Health Regulation No. 7 of 2019 classifies hospital waste as hazardous and toxic medical waste and regulates its management procedures accordingly. This study aims to analyze the management of hazardous and toxic solid medical waste at Purworejo Hospital, focusing on the stages of reduction, segregation, storage, transportation, and the use of personal protective equipment (PPE). This research employed a descriptive qualitative approach with a cross-sectional design. Data were collected through observations, interviews, and document reviews. The interviews involved both key informants and triangulation informants. The results revealed that the management of hazardous and toxic solid medical waste at Purworejo Hospital achieved a compliance rate of 74.58% categorized as “appropriate” and 25.442% categorized as “not yet appropriate.” This compliance rate remains below the required standard as stipulated in the Ministry of Health Regulation No. 7 of 2019. Non-compliance was identified in several aspects, including the absence of a designated pathway and special trolley for waste transportation, the lack of hepatitis and tetanus immunization for staff, and inconsistencies in the use of PPE.